Evaluation of brain-targeted chitosan nanoparticles through blood–brain barrier cerebral microvessel endothelial cells. (3rd October 2017) - Sahin, Adem; Yoyen-Ermis, Digdem; Caban-Toktas, Secil; Horzum, Utku; Aktas, Yesim; Couvreur, Patrick; Esendagli, Gunes; Capan, Yilmaz
Abstract: The blood–brain barrier (BBB) is the major problem for the treatment of central nervous system diseases. A previous study from our group showed that the brain-targeted chitosan nanoparticles-loaded with large peptide moieties can rapidly cross the barrier and provide neuroprotection. The present study aims to determine the efficacy of the brain-targeted chitosan nanoparticles' uptake by the human BBB cerebral microvessel endothelial cells (hCMECs) and to investigate the underlying mechanisms for enhanced cellular entry. Fluorescently labelled nanoparticles either conjugated with antibodies recognising human transferrin receptor (anti-TfR mAb) or not were prepared, characterised and their interaction with cerebral endothelial cells was evaluated. The antibody decoration of chitosan nanoparticles significantly increased their entry into hCMEC/D3 cell line. Inhibition of cellular uptake by chlorpromazine indicated that the anti-TfR mAb-conjugated nanoparticles were preferentially cell internalised through receptor-mediated endocytosis pathway. Alternatively, as primarily observed with control chitosan nanoparticles, aggregation of nanoparticles may also have induced macropinocytosis.